EP593 Clinicopathological features of endometrial carcinoma without abnormal uptake of 18F-fluorodeoxyglucose on pretreatment PET/CT. (1st November 2019) - Otsuka, I; Matsuura, T; Machida, Y
Abstract : Introduction/Background: PET/CT is an effective imaging modality in evaluating the aggressiveness of a tumour and detecting metastasis. In endometrial carcinoma, degree of 18F-fluorodeoxyglucose (FDG) uptake is associated with tumour grade, myometrial invasion, and extrauterine disease. However, in some types of endometrial carcinoma 18F-FDG uptake is not observed in the uterus whereas biopsy of the endometrium shows a carcinoma. To identify clinical and pathological features of these tumours, we performed a retrospective study. Methodology: Patients who received pretreatment 18F-FDG PET/CT and underwent staging surgery between 2006 and 2016 at our institution were investigated. Results: Seventeen cases of endometrial carcinoma without abnormal uptake of 18F-FDG on pretreatment PET/CT were identified. The median age was 62 years (range, 53–73 years). FIGO stage of the disease was IA in 13, IB in 1, II in 2, and IIIC1 in 1 patient. Histology of the tumour was endometrioid carcinoma grade 1 in 6, grade 2 in 2, grade 3 in 2, clear cell carcinoma in 2 and serous carcinoma in 5 patients. Seven patients received PET/CT after dilatation and curettage, and in two of these patients, no residual disease was detected pathologically in the removed uterus. Lymphatic space invasion was observed in three patients, and another patient with serous carcinoma with superficial invasion had pelvic lymph node metastasis and serosal involvement. Tumour recurrence developed in four patients and all of them had a serous carcinoma. The site of recurrence was the abdominal cavity in 2, the lung in 1, and the vaginal stump in 1 patient. Of these, three patients who developed a distant metastasis died of the disease. Conclusion: Patients with endometrial carcinoma without pretreatment FDG uptake in the uterus usually have a lower stage disease with good prognosis but may have serous carcinoma with poor prognosis. Disclosure: Nothing to disclose.